Maternal near miss events, an obstetrician’s nightmare - S., Kalyani; S. S., Prashanthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Near-miss obstetric cases are those who have survived childbirth after a life-threatening complication of pregnancy. The aim of this study is to assess the prevalence of maternal near miss events, fetomaternal outcome and alongside analyze the importance of high dependency unit care for near miss patients in reducing maternal morbidity and mortality. Methods: This hospital based cross-sectional study was conducted in the obstetrics and gynaecology department of Southern railway hospital during June 2019 July 2021. In this study, pregnant or postnatal women with life threatening complications are admitted to the HDU using SAMM composite score and maternal & perinatal outcome are documented. Data entry was done in Microsoft Excel and data were analyzed using Epi Info software (7.1.0.6). Results: Many indicators of maternal near miss are calculated. The incidence of near-miss events was 11.5/1,000 live births. The ratio of near-miss to maternal mortality was 7:1. Hypertensive disorders complicating pregnancy and Obstetric haemorrhage were the most common direct and cardiac diseases complicating pregnancies were the most common indirect causes of admission into HDU care. Conclusions: Evaluation of maternal near miss events provides a good sense about our deficiencies in referral system, treatment protocols and any delay in admission to intervention time. Good maternal outcome after HDU care in MNM patients and also cost-effective benefits.